The sense of music education in education conceived as an engine of the knowledge economy: a philosophical framework proposal - Fernández-Jiménez, Antonio; Jorquera-Jaramillo, María-Cecilia (Revista Electrónica Complutense de Investigación en Educación Musical - RECIEM, 2017)
Changes produced by the Knowledge-based Society and Economy have an influence on educational policies, attaching less importance to arts and music education within the curriculum. This article offers a literature review on present music education, where two opposite perspectives were found in: economic and social. The latter educational perspective aims the development of multiple human aspects in order to participate in current society. Music contributes to this goal, generating knowledge and action by means of it. To achieve this, philosophical thinking on music education, able to give fundament to music education and to respond to relevant topics for current education, should be elaborated.
Keywords: Music education; educational perspectives; philosophy of music education; knowledge-based society; knowledge-based economy.